Evaluating spoke facilitation costs of implementing TelePain in the Veterans Health Administration - Alexandra L. Rose; Shaina Coogan; Jess Indresano; Steven B. Zeliadt; Jessica A. Chen (Implementation Science Communications)
Abstract Background The high prevalence and significant morbidity and mortality associated with chronic pain among veterans has made expansion of pain services within the Veterans Health Administration (VHA) a key priority. TelePain, in which services are provided via telehealth from central “hub” sites to patients at decentralized “spoke” sites, is one such model with positive implementation findings to date. However, the staff effort and cost of implementation have yet to be examined when considering TelePain or similar virtual hub-and spoke models of specialty pain care, information that is critical for expansion of services. Methods Using an established time-based activity tracker designed for implementation facilitation, study staff tracked minutes spent on implementation activities at 11 spoke sites. Annual salaries were extracted to calculate an average cost per minute for each personnel type. Costs per personnel minute were combined with activity data to calculate costs of implementation activities at spoke sites. Implementation reach outcomes for the first 36 months of implementation were extracted from the electronic health record. Service utilization data was combined with cost data to calculate cost per patient reached and per clinical encounter achieved at each site. Results Total facilitation costs (range: $1,746-$7,978) and unique patients reached (range: 2–46) varied considerably across spoke sites and greater staff implementation efforts (measured in time or cost) were not associated with greater numbers of patients reached. Therefore, costs per patient reached also varied widely (range: $120–2,569) across spoke sites. Key challenges included high rurality and small clinic size; insufficient engagement of frontline providers; lack of referral options for high acuity patients; and lack of existing programming within which to situate pain services. Conclusions At spoke sites where patients were consistently referred and reached, costs were relatively modest, particularly compared to the high cost of untreated chronic pain, suggesting the potential impact of this model at scale. However, in spoke sites where referrals and encounters were low during initial implementation, cost per patient was high. Findings highlight the need for better methods for tailoring of facilitation interventions to spoke site’s individual needs to maximize impact.